Community-Based Digital Extension to Strengthen Local Food Resilience under Climate Uncertainty - Dance Tangkesalu MP (CV. Rayyan Dwi Bharata, 2025)
Climate uncertainty poses challenges to agricultural sustainability and local food security, especially in rural areas that still rely on traditional counseling. This study aims to analyze the effectiveness of community-based digital extension in strengthening food security through increasing access to climate information and farmers' adaptive capabilities. The research was conducted in Parigi Moutong Regency, Central Sulawesi, which has the characteristics of an agrarian community, is affected by climate change, and has the potential to apply digital technology. Using a mixed methods approach, the study involved 80 farmer households as survey respondents and 5 key informants consisting of agricultural extension workers, community leaders, farmer group leaders, and farmers who are active users of the digital platform. Quantitative data was analyzed with descriptive statistics and paired t-tests, while qualitative data were processed through thematic analysis. The results showed that the use of community-based digital extension platforms increased farmers' access to climate information, improved adaptive farming practices, and improved household food diversity scores within three months of implementation. This study concludes that the integration of digital extension in the community agribusiness system in Parigi Moutong is an effective strategy to strengthen adaptive and sustainable local food security in the midst of climate uncertainty.